Tremelimumab in Combination With Microwave Ablation in Patients With Refractory Biliary Tract Cancer. Issue 5 (10th March 2019) - Xie, Changqing; Duffy, Austin G.; Mabry‐Hrones, Donna; Wood, Bradford; Levy, Elliot; Krishnasamy, Venkatesh; Khan, Javed; Wei, Jun S.; Agdashian, David; Tyagi, Manoj; Gangalapudi, Vineela; Fioravanti, Suzanne; et al.
Abstract : Treatment options for patients with advanced biliary tract cancer are limited. Dysregulation of the immune system plays an important role in the pathogenesis of biliary tract cancer (BTC). This study aimed to investigate whether tremelimumab, an anti‐CTLA4 (cytotoxic T‐lymphocyte–associated protein 4) inhibitor, could be combined safely with microwave ablation to enhance the effect of anti‐CTLA4 treatment in patients with advanced BTC. Patients were enrolled to receive monthly tremelimumab (10 mg/kg, intravenously) for six doses, followed by infusions every 3 months until off‐treatment criteria were met. Thirty‐six days after the first tremelimumab dose, patients underwent subtotal microwave ablation. Interval imaging studies were performed every 8 weeks. Adverse events (AEs) were noted and managed. Tumor and peripheral blood samples were collected to perform immune monitoring and whole‐exome sequencing (WES). Twenty patients with refractory BTC were enrolled (median age, 56.5 years). No dose‐limiting toxicities were encountered. The common treatment‐related AEs included lymphopenia, diarrhea, and elevated transaminases. Among 16 patients evaluable for efficacy analysis, 2 (12.5%) patients achieved a confirmed partial response (lasting for 8.0 and 18.1 months, respectively) and 5 patients (31.3%) achieved stable disease. Median progression free survival (PFS) and overall survival (OS) were 3.4 months (95% confidence interval [CI], 2.5‐5.2) and 6.0 months (95% CI, 3.8‐8.8), respectively. Peripheral blood immune cell subset profiling showed increased circulating activated human leukocyte antigen, DR isotype ([HLA‐DR] positive) CD8 + T cells. T‐cell receptor (TCR)β screening showed tremelimumab expanded TCR repertoire, but not reaching statistical significance ( P  = 0.057). Conclusion : Tremelimumab in combination with tumor ablation is a potential treatment strategy for patients with advanced BTC. Increased circulating activated CD8 + T cells and TCR repertoire expansion induced by tremelimumab may contribute to treatment benefit.